Quantitative Fetal Fibronectin to Predict Spontaneous Preterm Birth: A Review - Hezelgrave, Natasha L (Womens Health (Lond), 2016)
Spontaneous preterm birth (sPTB) is the leading cause of neonatal morbidity and mortality globally. Accurate prediction of sPTB would enable targeting of interventions such as admission to hospital, antenatal corticosteroids, magnesium sulphate and in utero transfer as well as guiding prophylactic treatment (e.g., cerclage or progesterone). Measurement of fetal fibronectin concentration in the cervicovaginal fluid is a known predictor of sPTB. Traditionally a positive/negative test (defined by a threshold of 50 ng/ml), recent work has demonstrated improved prediction when used as a quantitative test, whereby the concentration of fetal fibronectin is measured by an automated bedside reader. This review examines the evidence surrounding the use of quantitative fetal fibronectin in asymptomatic women at high risk of sPTB, as well as those with symptoms of threatened sPTB.